The Landscape, the Swampland and the Era of Precision Cosmology. Issue 1 (20th November 2018) - Akrami, Yashar; Kallosh, Renata; Linde, Andrei; Vardanyan, Valeri
Abstract: We review the advanced version of the KKLT construction and pure d = 4 de Sitter supergravity, involving a nilpotent multiplet, with regard to various conjectures that de Sitter state cannot exist in string theory. We explain why we consider these conjectures problematic and not well motivated, and why the recently proposed alternative string theory models of dark energy, ignoring vacuum stabilization, are ruled out by cosmological observations at least at the 3σ level, i.e. with more than 99.7% confidence. Abstract : The authors start by reviewing the advanced version of the KKLT construction and pure d = 4 de Sitter supergravity, involving a nilpotent multiplet, with regard to various conjectures that de Sitter state cannot exist in string theory. It is explained why these conjectures are problematic and not well motivated, and why the recently proposed alternative string theory models of dark energy, ignoring vacuum stabilization, are ruled out by cosmological observations at least at the 3σ level, i.e. with more than 99.7% confidence.